The Effect of Digital Platform Adoption on the Performance of Cirebon Traditional Culinary MSMEs: A Technology Acceptance Model Analysis - Bahtiar; Indra Surya Permana; Chasan Bisri (CV Putra Publisher, 2026)
Digital transformation has changed how micro, small, and medium enterprises (MSMEs) market their products and build operational efficiency, including in the regional culinary sector. This study aims to analyze the effects of perceived ease of use (PEOU), perceived usefulness (PU), and attitude toward use (ATU) on behavioral intention (BI) to use digital platforms, as well as the impact of BI on actual use (AU) among traditional culinary MSMEs in Cirebon. The study employed a quantitative explanatory approach with a cross-sectional survey of 165 Cirebon culinary MSME owners who use digital platforms such as GoFood, ShopeeFood, GrabFood, Instagram, TikTok Shop, and WhatsApp Business. Data were collected using a 1-7 Likert scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that PEOU has a positive and significant effect on BI (beta = 0.384; t = 4.374; p < 0.001), and PU has a positive and significant effect on BI (beta = 0.235; t = 2.963; p = 0.004). However, ATU does not significantly affect BI (beta = 0.129; t = 1.632; p = 0.105). Furthermore, BI has a positive and significant effect on AU (beta = 0.339; t = 4.105; p < 0.001). The R-squared values are 0.357 for BI and 0.115 for AU. These findings confirm that ease of use and perceived usefulness are the primary drivers of digital platform adoption intention, while positive attitude alone is insufficient to drive usage intention in the context of Cirebon culinary MSMEs.